The Effect of Light Exposure to Bilirubine Levels on Serum Jaundice Infant in Hospital of Islamic NU Demak - Eko Naning Sofyanita; Endang Susilowaty; Roni Afriansya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Bilirubin is a substance formed from the normal breakdown of erythrocytes in the body so that it gives a yellow color to the stool and urine. The test of bilirubin in the laboratory must avoid exposure to light, which can cause decreased serum bilirubin levels by up to 50% in 1 hour due to disruption of the bilirubin's stability. This study is a cross-sectional analytic study of primary data using 30 samples of jaundice baby serum and direct and total bilirubin test. Data collection was conducted from the primary data by a direct test using 40 samples of infant jaundice and test of direct bilirubin and total bilirubin using methods Dichlorophenyl Diazonium. The results of the tests of 40 samples can result in the mean levels of total bilirubin were exposed to the light of 8.58 mg/dl and were not exposed to light 12,67mg /dl. Direct bilirubin levels mean that exposure to light is 3.98 mg/dl. In contrast, the unexposed light of 8.71 mg/dl, so that it can be concluded that the levels of total and direct bilirubin in serum jaundice infants exposed to lower light compared with those not exposed to light.